Risk-Based Supervision of Pension Funds : A Review of International Experience and Preliminary Assessment of the First Outcomes - Brunner, Gregory; Hinz, Richard; Rocha, Roberto (World Bank, Washington, DC, 2012)
This paper provides a review of the design and experience of risk-based pension fund supervision in several countries that have been leaders in the development of these methods. The utilization of risk-based methods originates primarily in the supervision of banks. In recent years it has increasingly been extended to other types of financial intermediaries including pension funds and insurers. The trend toward risk-based supervision of pensions is closely associated with movement toward the integration of pension supervision with that of banking and other financial services into a single national authority. Although similar in concept to the techniques developed in banking, the application to pension funds has required modifications, particularly for defined contribution funds that transfer investment risk to fund members. The countries examined provide a range of experiences that illustrate both the diversity of pension systems and approaches to risk-based supervision, but also a commonality of the focus on sound risk management and effective supervisory outcomes. The paper provides a description of pension supervision in Australia, Denmark, Mexico and the Netherlands, and an initial evaluation of the results achieved in relation to the underlying objectives.